Prevalence of depressive symptoms and signs of dementia in the elderly in the community - Maicon Henrique Lentsck; Calíope Pilger; Elismara Prates Schoereder; Kelly Holanda Prezotto; Thais Aidar de Freitas Mathias (Universidade Federal de Goias, 2015)
A cross-sectional study that analyzed the prevalence of depressive symptoms, signs of dementia and associated factors in seniors residing in a city located in the south of Brazil. A house survey was conducted in a sample of 359 seniors registered in the Basic Health Units, using the questionnaire Brazil Old Age Schedule. To analyze associated factors, Chi-Square test and Prevalence Ratio were calculated. The prevalence of depressive symptoms was 65,2%, higher for women (PR = 1,2; p=0,029) and for elders living alone (PR=1,3; p=0,009). Dementia signs were present in 37,69%, they were more frequent in women (PR=1,8; p<0,001), elders of 70 to 79 years (PR=1,4; p=0,014), of 80 or more years (PR=1,6; p=0,015), widowed (PR=1,7; p<0,001) and illiterate (RP=2,8; p<0,001). It is essential to comprehend the associated factors to depressive symptoms and signs of dementia to improve mental health actions for the elderly in the community, especially for women, widowed, those aged more than 70 years, illiterate and those living alone.